Evaluating the Effects of Cerebrospinal Fluid Protein Content on the Performance of Differential Pressure Valves and Antisiphon Devices Using a Novel Benchtop Shunting Model. Issue 5 (10th June 2020) - Gorelick, Noah L; Serra, Riccardo; Iyer, Rajiv; Um, Richard; Grewal, Angad; Monroe, Audrey; Antoine, Hannah; Beharry, Kelly; Cecia, Arba; Kroll, Francesca; Ishida, Wataru; Perdomo-Pantoja, Alexander; et al.
Abstract: BACKGROUND: Hydrocephalus is managed by surgically implanting flow-diversion technologies such as differential pressure valves and antisiphoning devices; however, such hardware is prone to failure. Extensive research has tested them in flow-controlled settings using saline or de-aerated water, yet little has been done to validate their performance in a setting recreating physiologically relevant parameters, including intracranial pressures, cerebrospinal fluid (CSF) protein content, and body position. OBJECTIVE: To more accurately chart the episodic drainage characteristics of flow-diversion technology. A gravity-driven benchtop model of flow was designed and tested continuously during weeks-long trials. METHODS: Using a hydrostatic pressure gradient as the sole driving force, interval flow rates of 6 valves were examined in parallel with various fluids. Daily trials in the upright and supine positions were run with fluid output collected from distal catheters placed at alternating heights for extended intervals. RESULTS: Significant variability in flow rates was observed, both within specific individual valves across different trials and among multiple valves of the same type. These intervalve and intravalve variabilities were greatest during supine trials and with increased protein. None of the valves showed evidence of overt obstruction during 30 d of exposure to CSF containing 5 g/L protein. CONCLUSION: Day-to-day variability of ball-in-cone differential pressure shunt valves may increase overdrainage risk. Narrow-lumen high-resistance flow control devices as tested here under similar conditions appear to achieve more consistent flow rates, suggesting their use may be advantageous, and did not demonstrate any blockage or trend of decreasing flow over the 3 wk of chronic use.